Tigecycline-induced inhibition of mitochondrial DNA translation may cause lethal mitochondrial dysfunction in humans. (April 2018) - Vandecasteele, S.J.; Seneca, S.; Smet, J.; Reynders, M.; De Ceulaer, J.; Vanlander, A.V.; van Coster, R.
Abstract: Background: A 65-year-old patient developed an unexplained and ultimately lethal metabolic acidosis under prolonged treatment with tigecycline. Tigecycline is known to have a selective inhibitory effect on eukaryotic mitochondrial translation. The underlying molecular mechanisms of the metabolic acidosis in this patient were explored. Methods: Oxidative phosphorylation system (OXPHOS) analysis, blue native polyacrylamide gel electrophoresis followed by in-gel activity staining in mitochondria, molecular analysis of mitochondrial DNA (mtDNA) for genomic rearrangements and sequencing of the rRNA genes was performed on the subject's skeletal muscle. Results: OXPHOS analysis revealed a combined deficiency of the complexes I, III, IV and V, with a preserved function of complex II (encoded by nuclear DNA), thus demonstrating a defective mtDNA translation. There were no known underlying mitochondrial genetic defects. The patient had a (m.1391T>A) variant within the 12SrRNA gene in heteroplasmy (50–60%). Conclusions: This patient developed an ultimately lethal mitochondrial toxicity while receiving prolonged treatment with tigecycline, which was caused by a defective translation of the mtDNA. Tigecycline is known to suppress eukaryotic mitochondrial DNA translation, but until now this effect has been considered to be clinically insignificant. The observations in this patient suggest a clinically significant mitochondrial toxicity of tigecycline in this patient, and warrant further investigation.